2023
DOI: 10.3390/nu15061418
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Low-Carbohydrate Diet on Micronutrient Intake and Status in Adolescents with Type 1 Diabetes

Abstract: Objective: The aim of this study was to evaluate the macronutrient and micronutrient intake and status in youth with type 1 diabetes mellitus (T1DM) following the consumption of a low-carbohydrate diet (LCD). Research Methods and Procedures: In a prospective intervention clinical trial, adolescents with T1DM using a continuous glucose monitoring device were enrolled. Following a cooking workshop, each participant received a personalized diet regime based on LCD (50–80 g carbohydrate/day). A Food Frequency Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although the amount of carbohydrates in grams did not differ significantly before and after intervention, the proportion of carbohydrates in total calories was lower after the diet. This change might have contributed to the observed improvement in glycemic control, as seen in other studies [25]. The intensive nutritional monitoring program, conducted by a registered dietitian, might also have contributed to better glycemic control [26,27].…”
Section: Discussionmentioning
confidence: 58%
“…Although the amount of carbohydrates in grams did not differ significantly before and after intervention, the proportion of carbohydrates in total calories was lower after the diet. This change might have contributed to the observed improvement in glycemic control, as seen in other studies [25]. The intensive nutritional monitoring program, conducted by a registered dietitian, might also have contributed to better glycemic control [26,27].…”
Section: Discussionmentioning
confidence: 58%
“…In our study, we found more favorable glycemic effects after the HP and HF meals, which reflect the macronutrient composition of low carbohydrate diets (LCDs). LCDs have been found to reduce HbA1c in people with T2D [ 31 ] and T1D [ 32 ] and decrease time spent in hypoglycemia and glycemic variability in people with T1D [ 33 ]. Moreover, the higher MUFA content of our HP and HF meals resembles Mediterranean-style diets, which have shown beneficial long-term effects on CVD risk factors in T2D [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the proportion of body fat (especially visceral fat) and the reduction in lean mass is negatively related to glycemic and lipid metabolism, leading to worse glycemic control and the need for insulin dose increments in DM1 patients [ 10 , 11 , 12 ]. Changes in insulin sensitivity are due to the change in the secretory pattern of adipose tissue from lean to obese, where M2 macrophages can be replaced by M1, resulting in an increased gene expression and production of pro-inflammatory mediators that are released by adipose visceral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although DM1 patients traditionally tend to be underweight, the increase in sedentary lifestyles and exacerbated consumption of foods high in sugar and fat has contributed to weight gain in this population. It is known that an increase in the proportion of fat, especially visceral fat, and a reduction in lean mass worsen glycemic control and plasma lipid levels [ 10 , 11 , 12 ]. In addition, the increase in visceral adipose tissue to the detriment of the reduction in lean mass has direct implications for installing a pro-inflammatory scenario and oxidative stress that will strongly contribute to the micro and macro-vascular complications [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%